IMPLEMENTASI KURIKULUM MERDEKA SD NEGERI 2 KOTA TERNATE - Irawan, Iwan; La Ode Alumu, Wa Ode Murima; Amor, Regina Klaresia (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2024)
The implementation of the Merdeka Curriculum in SDN 2 Ternate City has been running gradually in classes I, II, IV and V. The purpose of this study were: 1) To find out the implementation of the Merdeka Curriculum in SDN 2 Ternate City, 2) to find out readiness teachers in the implementation of the Merdeka Curriculum in SDN 2 Kota Ternate, 3) to find out the obstacles faced by schools in the implementation of the Merdeka Curriculum in SDN 2 Ternate City. The results of this study showed that in implementation the curriculum in stages and in this curriculum the teacher is only a motivator for students, after that there are some teacher and school readiness, namely by preparing adequate facilities and infrastructure in implementing this curriculum, Attending the KKG, preparing a teaching module, as well as following the workshop held by the government. The problems in this curriculum are, lack of human resources, the existence of teachers who are technological staples, lack of teacher readiness, problems in planning, implementing, and assessing learning. One of the ways to overcome these problems is by finding sources on social media, following the KKG, attending PMO assistance, holding tutoring, making important notes, doing pretest, and attending training related to the independent curriculum.